Preparation method of modified PBO fiber toughening agent for well cementation under high-frequency alternating injection-production condition

Through the preparation method of modified PBO fiber toughening agent, the problem of cementing cement ring damage under high-frequency alternating injection and production conditions is solved, and the mechanical properties and seal integrity of cementing cement stone are improved in low temperature and acid-base environments, and the formation environmental requirements of hydrogen storage, helium storage and air energy storage wells are met.

CN119640581AInactive Publication Date: 2025-03-18SOUTHWEST PETROLEUM UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510162053.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Under high-frequency alternating injection and production conditions, conventional cementing cement rings are easily damaged, affecting their interlayer sealing effect. The fiber toughening agents of the prior art perform poorly in low temperature and acid-base environments, and are difficult to meet the formation environmental requirements of hydrogen storage, helium storage and air energy storage wells.

Method used

Using a modified PBO fiber toughening agent, the PBO fiber is soaked in acetone solution and mixed with heavy calcium carbonate, ethanol, silane coupling agent and other substances to form a modified solution, and then added ultrasonic cleaning is added to further modify the fibers, improving its surfactivity and bonding strength to the cement matrix.

Benefits of technology

The modified PBO fiber toughener exhibits good dispersion and bonding strength in low temperature and acid-base environments, significantly improving the mechanical properties and sealing integrity of cement cement stone, and meeting the formation conditions of the bottom-hole temperature of hydrogen, helium and air energy storage wells with less than 110℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640581A_ABST
    Figure CN119640581A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a modified PBO fiber toughening agent for well cementation under a high-frequency alternating injection-production condition, and belongs to the technical field of well cementation materials. The method comprises the following steps: obtaining PBO fibers; the method comprises the following steps: soaking PBO fibers in an acetone solution, cleaning and drying; weighing heavy calcium carbonate, ethanol, a silane coupling agent and deionized water, mixing and stirring to obtain a modified solution; pBO fibers are added into the modification solution, the mixture is placed in a magnetic stirrer to be stirred at a high speed for 30-90 min, and primary modified PBO fibers are obtained; and putting the primarily modified PBO fiber into a beaker containing deionized water, putting the beaker into an ultrasonic cleaner, and treating for 20-40 minutes to obtain the modified PBO fiber toughening agent. According to the present invention, the raw materials are cheap and easily available, the preparation process is controllable, the product performance is stable, the compatibility is good, and when the cement paste is used for the well cementation operation, the formation environment and the working condition faced by the air energy storage well can be met, and the success rate of the well cementation construction can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cementing materials, and specifically relates to a method for preparing a modified PBO fiber toughening agent for hydrogen storage, helium storage and air energy storage wells under high-frequency alternating injection and production conditions. Background Art

[0002] With the continuous deepening of oilfield exploration and development, hydrogen storage, helium storage and air energy storage wells have gradually become the focus of exploration and development. During the high-frequency cyclic injection and production process, conventional cement sheaths are easily damaged, which in turn affects the interlayer isolation function of cement sheaths. At present, the main practice is to add toughening materials to conventional cement slurry. Studies have shown that the addition of toughening materials, elastic materials, etc. can help improve the elastic toughness of cement stone and improve the long-term isolation capacity of cement sheaths.

[0003] Fiber materials are often used as toughening materials in cement-based materials, but long fibers are not easy to pump, and the difficulty of fiber mixing and dispersion limits the amount of fiber used. Since the actual amount of fiber added is less than 2%, the fiber length used in cementing materials does not exceed 10mm, which cannot better exert the performance of fibers in cement products such as mortar and concrete.

[0004] "Method for preparing cement slurry toughening agent, cement slurry and preparation method thereof" (CN113402186A), respectively modify carbon fiber and nanoparticles to obtain surface-modified carbon fiber and surface-modified nanoparticles, and obtain cement slurry toughening agent by chemical bonding. Due to its stability under high temperature conditions, it effectively improves the toughness of cement paste. "Method for preparing an inorganic fiber toughening agent for cement-based cementing of oil and gas wells" (CN11452119A), using a mixture of one or more fibers selected from nano-silicon dioxide-modified basalt fiber, carbon fiber, brucite fiber and silicon carbide fiber, and then using it as a toughening material, can reduce the brittleness of cement paste and improve the mechanical flexibility of cement paste. The above methods respectively use different technical means to toughen cement paste, but the treatment methods are mainly aimed at conventional oil and gas resource development, and are not suitable for formation conditions where the bottom hole temperature of hydrogen storage, helium storage and air energy storage wells is lower than 110°C. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions. The method has reliable principle, simple operation, cheap and readily available raw materials, controllable preparation process, stable product performance, and good compatibility. The method is applied to cementing cement slurry for cementing operations, which can meet the formation environment and working conditions faced by air energy storage wells, thereby improving the success rate of cementing construction.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.

[0007] The preparation method of modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions comprises the following steps in sequence: Step a, obtaining PBO fiber; Step b, modifying the PBO fiber to obtain a modified PBO fiber toughening agent, the process is as follows: Step b1, soaking the PBO fiber in an acetone solution, washing and drying; Step b2, weighing heavy calcium carbonate, ethanol, a silane coupling agent and deionized water, mixing and stirring to obtain a modified solution; Step b3, adding the PBO fiber obtained in step b1 to the modified solution, placing it in a magnetic stirrer, and stirring at high speed for 30 to 90 minutes to obtain the primary modified PBO fiber; Step b4: placing the initially modified PBO fiber in a beaker filled with deionized water, and treating it in an ultrasonic cleaner for 20 to 40 minutes to obtain a modified PBO fiber toughening agent.

[0008] Furthermore, in step b1, the drying conditions are: 60-80° C., and the time is 6-8 hours.

[0009] Furthermore, in the step b2, the mass ratio of heavy calcium carbonate, ethanol, silane coupling agent and deionized water is 10-30:40-50:2-5:1-2, and the mixing and stirring refers to stirring in a constant temperature magnetic stirrer at a temperature of 30-50°C for 30-90 minutes.

[0010] Furthermore, in step b2, the silane coupling agent is one of γ-aminopropyltriethoxysilane (KH-550), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), and γ-(methacryloyloxy)propyltrimethoxysilane (KH-570).

[0011] Furthermore, in step b4, the ultrasonic power is 250-300 W and the frequency is 25 kHz.

[0012] Furthermore, the PBO fiber in step a is obtained by the following steps: Step a1, weigh 5-15 parts of 85% phosphoric acid and 10-30 parts of 80% polyphosphoric acid by mass, add them into a four-necked bottle, and stir at a low speed under reduced pressure for 2 hours to obtain a composite solution; Step a2, adding 5-10 parts of 4,6-diaminobenzene hydrochloride to the composite solution, maintaining the temperature at 50-60° C., stirring at high speed for 10-20 hours, and removing HCl under reduced pressure during the reaction to obtain solution A; Step a3, adding 1-5 parts of terephthalic acid and 10-20 parts of P2O5 to solution A, reacting at 100°C for 24-48 hours, 150°C for 3-5 hours, 160°C for 8-10 hours, and 180°C for 15-25 hours, respectively, to obtain polymer A; Step a4, adding polymer A to methanol for precipitation, washing with water until neutral, filtering and drying, then heating and reflux with 10-20 parts of N,N-dimethylformamide and 100 parts of deionized water in sequence, filtering and drying for 24-48 hours to obtain PBO fiber.

[0013] The reaction process of PBO fiber is as follows:

[0014] Poly(p-phenylene benzobisoxazole) (PBO) is obtained by polycondensation with 4,6-diamino-1,3-diphenylphenol hydrochloride and terephthalic acid as raw materials and polyphosphoric acid as medium. Since the surface of PBO fiber is too smooth and the surface activity of the fiber is low, it is necessary to modify the surface of PBO fiber.

[0015] Silane coupling agent is a small molecule modifier, which is loaded on the powder surface by dehydration condensation. The coupling agent modified heavy calcium carbonate surface with epoxy groups, which easily react with the carboxyl groups on the surface of PBO fibers to form stronger chemical bonds, reduce the free energy of the fiber surface, increase the hydrophilicity, and improve the interfacial bonding strength between the fiber and the matrix, which is more conducive to the strength of the PBO fiber itself.

[0016] The modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions is used to prepare cement slurry, which is particularly suitable for cementing projects of hydrogen storage, helium storage and air energy storage wells.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The PBO fiber is further modified. On the basis of ensuring the original performance of the material, epoxy groups are introduced on the fiber surface to further improve the fiber surface activity and wetting ability, so that the fiber can better bond with the cement paste to ensure the mechanical properties and sealing integrity of the cement paste; (2) PBO fiber is a low-temperature, acid- and alkali-resistant material. Using modified PBO fiber as a toughening agent can basically meet the formation environmental conditions faced by existing air energy storage wells, while maintaining good engineering performance and ensuring cementing quality; (3) The hydrophilicity of the surface of the modified PBO fiber toughening agent will be improved, reducing its agglomeration phenomenon in water, ensuring that the modified PBO fiber has good dispersibility in the alkaline environment of cement slurry; secondly, the modified PBO fiber toughening agent inhibits the crack propagation of the cement stone matrix, improves the bonding strength between the fiber and the matrix, and thus improves the mechanical properties of the cementing cement stone; (4) The modified PBO fiber toughening agent is used in cementing cement, has no other adverse effects on the engineering properties of cement slurry, and can improve the high temperature stability and suspension of the slurry to a certain extent. At the same time, it has good compatibility with cementing cement admixtures, meets the needs of engineering construction, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of the present invention, and do not constitute a limitation of the embodiments of the present invention. In the drawings: Figure 1 This is the microstructure diagram of the modified PBO fiber toughening agent prepared in Example 1.

[0019] Figure 2 This is the stress-strain diagram of the cement paste in Example 1.

[0020] Figure 3 It is the stress-strain diagram of comparative cement paste. DETAILED DESCRIPTION

[0021] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0022] Sources of materials used in the examples of the present invention: The oil well cement used is Sichuan Jiahua G-grade high sulfur-resistant oil well cement.

[0023] The fluid loss reducer used was "Fluid Loss Reducer G33S for Oil Well Cement" commercially available from Weihui Chemical Co., Ltd.

[0024] The dispersant used was "dispersant USZ for oil well cement" commercially available from Weihui Chemical Co., Ltd.

[0025] The defoaming agent used was "Oil Well Cement Defoaming Agent DF-T" commercially available from Weihui Chemical Co., Ltd.

[0026] 1. Preparation of modified PBO fiber toughening agent for cementing

[0027] Example 1 Step a, obtaining PBO fiber, the process is as follows:

[0028] Step a1, weigh 5 parts of 85% phosphoric acid and 10 parts of 80% polyphosphoric acid by mass, add them into a four-necked bottle, and stir at a low speed under reduced pressure for 2 hours to obtain a composite solution; Step a2, adding 5 parts of 4,6-diaminobenzene hydrochloride to the composite solution, maintaining the temperature at 50° C., stirring at high speed for 10 hours, and removing HCl under reduced pressure during the reaction to obtain solution A; Step a3, using a microinjection pump to add 1 part of terephthalic acid and 10 parts of P2O5 to solution A, reacting at 100°C for 24h, 150°C for 3h, 160°C for 8h, and 180°C for 15h, respectively, to obtain polymer A; Step a4, adding polymer A to methanol for precipitation, washing with water until neutral, filtering with suction, drying, repeating for multiple times; then heating and reflux with 10 parts of N,N-dimethylformamide and 100 parts of deionized water in turn, filtering with suction, and drying for 24 hours to obtain PBO fiber; Step b, modifying the PBO fiber obtained in step a, comprises the following steps: Step b1, soaking the PBO fiber in an acetone solution, washing it and drying it for 6 hours to obtain washed PBO fiber, wherein the weight ratio of acetone to solvent is 1:10, and the solvent is clean water; Step b2, weighing heavy calcium carbonate, ethanol, KH-550 and deionized water, placing them in a constant temperature magnetic stirrer at 30°C and mixing them for 30 minutes to obtain a modified solution, wherein the mass ratio of heavy calcium carbonate, ethanol, KH-550 and deionized water is 10:40:2:1; Step b3, adding the washed PBO fiber to the modified solution, placing it in a magnetic stirrer, and stirring at high speed for 30 minutes to obtain the primary modified PBO fiber; Step b4, placing the initially modified PBO fiber in an ultrasonic cleaner with a power of 250 W and a treatment time of 20 min to obtain a modified PBO fiber toughening agent.

[0029] Example 2 Step a, obtaining PBO fiber, the process is as follows: Step a1, weigh 10 parts of 85% phosphoric acid and 20 parts of 80% polyphosphoric acid by mass, add them into a four-necked bottle, and stir at a low speed under reduced pressure for 2 hours to obtain a composite solution; Step a2, adding 5 parts of 4,6-diaminobenzene hydrochloride to the composite solution, maintaining the temperature at 55° C., stirring at high speed for 15 hours, and removing HCl under reduced pressure during the reaction to obtain solution A; Step a3, using a microinjection pump to add 5 parts of terephthalic acid and 15 parts of P2O5 to solution A, reacting at 100°C for 36 hours, 150°C for 4 hours, 160°C for 9 hours, and 180°C for 20 hours, respectively, to obtain polymer A; Step a4, adding polymer A to methanol for precipitation, washing with water until neutral, filtering with suction, drying, repeating for multiple times; then heating and reflux with 15 parts of N,N-dimethylformamide and 100 parts of deionized water in turn, filtering with suction, and drying for 36 hours to obtain PBO fiber; Step b, modifying the PBO fiber obtained in step a, comprises the following steps: Step b1, soaking the PBO fiber in an acetone solution, washing it and drying it for 7 hours to obtain washed PBO fiber, wherein the weight ratio of acetone to solvent is 1:15, and the solvent is clean water; Step b2, weighing heavy calcium carbonate, ethanol, KH-560 and deionized water, placing them in a constant temperature magnetic stirrer at 40°C and mixing them for 60 minutes to obtain a modified solution, wherein the mass ratio of heavy calcium carbonate, ethanol, KH-560 and deionized water is 20:45:3:2; Step b3, adding the washed PBO fiber to the modified solution, placing it in a magnetic stirrer, and stirring at high speed for 60 minutes to obtain the primary modified PBO fiber; Step b4: placing the initially modified PBO fiber in an ultrasonic cleaner at a power of 270 W for a treatment time of 30 min to obtain a modified PBO fiber toughening agent.

[0030] Example 3 Step a, obtaining PBO fiber, the process is as follows: Step a1, weigh 15 parts of 85% phosphoric acid and 30 parts of 80% polyphosphoric acid by mass, add them into a four-necked bottle, and stir at a low speed under reduced pressure for 2 hours to obtain a composite solution; Step a2, adding 10 parts of 4,6-diaminobenzene hydrochloride to the composite solution, maintaining the temperature at 60° C., stirring at high speed for 20 hours, and removing HCl under reduced pressure during the reaction to obtain solution A; Step a3, using a microinjection pump to add 5 parts of terephthalic acid and 20 parts of P2O5 to solution A, reacting at 100°C for 48 hours, 150°C for 5 hours, 160°C for 10 hours, and 180°C for 25 hours, respectively, to obtain polymer A; Step a4, adding polymer A to methanol for precipitation, washing with water until neutral, filtering with suction, drying, repeating for multiple times; then heating and reflux with 20 parts of N,N-dimethylformamide and 100 parts of deionized water in turn, filtering with suction, and drying for 28 hours to obtain PBO fiber; Step b, modifying the PBO fiber obtained in step a, comprises the following steps: Step b1, soaking the PBO fiber in an acetone solution, washing it and drying it for 8 hours to obtain washed PBO fiber, wherein the weight ratio of acetone to solvent is 1:20, and the solvent is ethanol; Step b2, weighing heavy calcium carbonate, ethanol, KH-570 and deionized water, placing them in a constant temperature magnetic stirrer at 50° C. and mixing and stirring for 90 minutes to obtain a modified solution, wherein the mass ratio of heavy calcium carbonate, ethanol, KH-570 and deionized water is 30:50:5:2; Step b3, adding the washed PBO fiber to the modified solution, placing it in a magnetic stirrer, and stirring at high speed for 90 minutes to obtain the primary modified PBO fiber; Step b4: placing the initially modified PBO fiber in an ultrasonic cleaner at a power of 300 W for a treatment time of 40 min to obtain a modified PBO fiber toughening agent.

[0031] 2. Performance test of modified PBO fiber toughening agent for cementing:

[0032] The cement slurry was prepared according to GBT19139-2012 “Test Methods for Oil Well Cement”, with the formula: G-grade oil well cement + 1% toughening agent + 0.5% dispersant + 0.5% fluid loss reducer + 0.2% defoamer, where the water-cement ratio was 0.44.

[0033] Comparative Example: The cement slurry formula does not contain a toughening agent, and the other components are the same.

[0034] 1. SEM test The modified PBO toughening agent for cementing prepared in Example 1 was tested by scanning electron microscope (SEM). The test results are as follows: Figure 1 As shown, the toughening agent has granular oligomers on its surface with a rough morphology, which effectively increases the physical flexibility and roughness of the PBO fiber surface and helps to form a good bond between the fiber and the cement matrix.

[0035] 2. Engineering performance test of cement slurry system According to GBT19139-2012 “Test methods for oil well cement”, the engineering performance tests of the cementing slurries of Examples 1-3 and the comparative example were carried out. The test results are shown in Table 1.

[0036]

[0037] As can be seen from Table 1, the toughening agent provided by the present invention has little effect on the density and fluidity of cement slurry. After adding the toughening agent, the cement slurry has lower free liquid and water loss, and the thickening curve is stable, without the phenomenon of centering and bulging, and the thickening time is controllable. The comprehensive performance of the cement slurry system meets the requirements of cementing construction in high temperature environment.

[0038] 3. Compressive strength test of cement stone at different ages The cement slurries of Examples 1-3 and the comparative example were placed in a 90°C×20.7MPa curing kettle and cured for 3d, 7d, 14d and 28d respectively. The compressive strength and tensile strength of the cement paste were tested to evaluate the reinforcing effect of the modified PBO fiber toughening agent on the oil well cement paste. The test results are shown in Tables 2 and 3.

[0039]

[0040]

[0041] According to the test results in Table 2, the cementing cement stone to which the modified PBO fiber toughening agent provided by the present invention is added has a significantly increased compressive strength of 70-80% compared with the comparative example after curing at 90°C (clean water) for 3d and 7d, indicating that the excellent dispersibility of the toughening agent makes the structure of the cement stone more uniform and dense, and the compressive capacity of the cementing cement stone is guaranteed. At the same time, the dispersion of the toughening agent in cement is enhanced, which helps to be more evenly distributed in the cement stone and effectively disperse the load energy of the cement stone.

[0042] According to the test results in Table 3, compared with the comparative cement stone without any toughening agent, the tensile strength of the cement stone containing the modified PBO fiber toughening agent provided by the present invention is increased by 13-20% at 3d. It can be seen that the modified PBO fiber has a significant toughening effect on cement stone. The surface roughness of the toughening agent after modification is increased, making the fiber and the cement matrix more closely bonded.

[0043] 4. Alternating load test of cement stone Figure 2 , Figure 3 They are respectively the axial stress-strain curves of cement stone of Example 1 and Comparative Example under a confining pressure of 20 MPa. In the first two cycles, the stress-strain curve of cement stone forms an obvious hysteresis loop with obvious plastic strain. As the cyclic loading and unloading continues, the hysteresis curve becomes more and more dense and reaches stability. The hysteresis curve continuously moves backward in a stable shape, and the plastic strain continuously accumulates in a linear variation law. After the 30th cycle of Example 1, the plastic strain is reduced by 0.1548% compared with the comparative example, indicating that Example 1 has better toughness.

[0044] Compared with other existing cementing tougheners, after curing for 3 days at 90°C (clean water), the compressive strength of cement paste mixed with PVA fiber toughener and PI fiber toughener were 30.89 MPa and 31.54 MPa, respectively, with an increase of 20-30%. The modified PBO fiber toughener can significantly improve the compressive strength of cement paste by 70-80%, far exceeding the above tougheners. Compared with other tougheners, the modified PBO fiber toughener can not only significantly improve the compressive strength of cement paste, but also effectively enhance its durability and crack resistance, providing more reliable technical support for cementing projects.

[0045] In summary, the modified PBO fiber toughening agent has good compatibility with the cement matrix and can significantly improve the mechanical properties of cement paste. The toughening agent can be evenly distributed in the cement paste, reducing the pores of the cement matrix, not only improving the compressive strength of the cement paste, but also inhibiting the generation of fine cracks, and has a wide range of application potential.

[0046] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions, characterized in that: The following steps are included in sequence: Step a, obtaining PBO fiber; Step b, modifying the PBO fiber to obtain a modified PBO fiber toughening agent, the process is as follows: Step b1, soaking the PBO fiber in an acetone solution, washing and drying; Step b2, weighing heavy calcium carbonate, ethanol, a silane coupling agent and deionized water, mixing and stirring to obtain a modified solution; Step b3, adding the PBO fiber obtained in step b1 to the modified solution, placing it in a magnetic stirrer, and stirring at high speed for 30 to 90 minutes to obtain the primary modified PBO fiber; Step b4: placing the initially modified PBO fiber in a beaker filled with deionized water, and treating it in an ultrasonic cleaner for 20 to 40 minutes to obtain a modified PBO fiber toughening agent.

2. The method for preparing a modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions as claimed in claim 1, characterized in that: In the step b1, the drying conditions are: 60-80° C., and the drying time is 6-8 hours.

3. The method for preparing a modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions as claimed in claim 1, characterized in that: In the step b2, the mass ratio of heavy calcium carbonate, ethanol, silane coupling agent and deionized water is 10-30:40-50:2-5:1-2, and the mixing and stirring refers to stirring in a constant temperature magnetic stirrer at a temperature of 30-50° C. for 30-90 min.

4. The method for preparing a modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions as claimed in claim 1, characterized in that: In the step b2, the silane coupling agent is one of KH-550, KH-560 and KH-570.

5. The method for preparing a modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions as claimed in claim 1, characterized in that: In step b4, the ultrasonic power is 250-300 W and the frequency is 25 kHz.

6. The method for preparing a modified PBO fiber toughening agent for cementing under high-frequency alternating injection and production conditions as claimed in claim 1, characterized in that: In step a, the PBO fiber is obtained by the following steps: Step a1, weigh 5-15 parts of 85% phosphoric acid and 10-30 parts of 80% polyphosphoric acid by mass, add them into a four-necked bottle, and stir at a low speed under reduced pressure for 2 hours to obtain a composite solution; Step a2, adding 5-10 parts of 4,6-diaminobenzene hydrochloride to the composite solution, maintaining the temperature at 50-60° C., stirring at high speed for 10-20 hours, and removing HCl under reduced pressure during the reaction to obtain solution A; Step a3, adding 1-5 parts of terephthalic acid and 10-20 parts of P2O5 to solution A, reacting at 100°C for 24-48 hours, 150°C for 3-5 hours, 160°C for 8-10 hours, and 180°C for 15-25 hours, respectively, to obtain polymer A; Step a4, adding polymer A to methanol for precipitation, washing with water until neutral, filtering and drying, then heating and reflux with 10-20 parts of N,N-dimethylformamide and 100 parts of deionized water in sequence, filtering and drying for 24-48 hours to obtain PBO fiber.

7. A modified PBO fiber toughening agent prepared by the method of claim 1, 2, 3, 4, 5 or 6, characterized in that: It is used to prepare cement slurry, which is suitable for cementing projects of hydrogen storage, helium storage and air energy storage wells.

Citation Information

Patent Citations

  • Preparation method of cement paste flexibilizer, cement paste and preparation method of cement paste

    CN113402186A

  • Nano inorganic powder coated high molecular fiber and its preparing method

    CN101050595A

  • High-performance wave-transmitting composite material based on PBO (poly-p-phenylene benzobisthiazole) fiber and preparation method thereof

    CN102675825A

  • Surface modifying method of PBO (polybenzoxazole) fiber

    CN102808325A

  • Anti-static macromolecular power cable material and preparation method thereof

    CN106009196A